Effectiveness of Official Assessment System for PBB-P2 Tax Collection in Bekasi City - Rafi Tri Darmawan; Nurikah; Ahmad Lanang Citrawan (Studia : Journal of Humanities and Education Studies, 2025)
This study aims to analyze the effectiveness of the application of the Official Assessment System on land and Building Tax rural and Urban (PBB-P2) in Bekasi, as well as identify obstacles and solutions implemented Bapenda in improving taxpayer compliance. This study uses a normative-empirical approach with reference to the theoretical framework of taxation, public administration, and legal effectiveness as proposed by Soekanto, Rahardjo, and Mardiasmo. The results showed that the official determination system has been running quite optimally based on the achievement of the target realization of PBB-P2, but still encountered obstacles in the form of arrears, inaccuracy of tax object data, as well as low tax literacy in a number of Regions. Bapenda Bekasi responds to this problem through modernization of digital-based tax services, expansion of payment channels, improvement of data quality, and intensification of socialization to taxpayers. Analysis based on the theory of legal effectiveness confirms that the success of tax collection is determined not only by regulation, but also by the support of implementing structures, the legal culture of society, and service facilities. This study confirms the need for integration of policy, technology, and public education to strengthen the sustainability of PBB-P2 acceptance as a source of regional income.